Observation of Intermittency‐Induced Critical Dynamics in Geomagnetic Field Time Series Prior to the Intense Magnetic Storms of March, June, and December 2015. Issue 6 (14th June 2018) - Balasis, Georgios; Daglis, Ioannis A.; Contoyiannis, Yiannis; Potirakis, Stelios M.; Papadimitriou, Constantinos; Melis, Nikolaos S.; GIannakis, Omiros; Papaioannou, Athanasios; Anastasiadis, Anastasios; Kontoes, Charalampos
Abstract: Criticality has been proposed as a suitable framework to study the nonlinear system of the Earth's magnetosphere. The magnetic field variations observed by the midlatitude HellENIc GeoMagnetic Array with respect to the most intense magnetic storms (Dst <− 150 nT) of the current solar cycle (i.e., 17 March, 23 June, and 20 December 2015) are analyzed using the method of critical fluctuations. We show that the application of method of critical fluctuation to the HellENIc GeoMagnetic Array time series reveals the existence of intermittency‐induced criticality in the range of 6 to 45 hr prior to the onset of these events. The results suggest that the underlying dynamical processes in the magnetosphere prior to intense magnetic storms present dynamics analogous to those of thermal systems undergoing second‐order phase transition. Our findings demonstrate that the proposed method can be very relevant for the analysis of critical fluctuations in the framework of space systems. Key Points: We show the existence of criticality in geomagnetic field data between 6 and 45 hr before the strongest magnetic storms of solar cycle 24 The dynamics of the magnetosphere prior to storms is analogous to the dynamics of thermal systems undergoing second‐order phase transition Space weather forecasting schemes could take into account these findings and implement them as potential precursors of storm activity